Deceptive Cypripedium calceolus shares more floral scent compounds with co-flowering rewarding species than those species share among each other - Etl, Corinna; Etl, Florian; Guilhot, Robin; Braunschmid, Herbert; Gross, Karin; Dötterl, Stefan (Frontiers in Plant Science, 2025)
The vast majority of flowering plants depend on animal pollinators for sexual reproduction. These plants usually provide a reward, such as nectar and/or pollen, to their pollinators, and floral scent is often key to attract them. Some plants, however, do not provide any such reward, though they advertise one. Even though it is well known that such a food-deceptive pollination strategy is particularly common in orchids, the role of floral scent in attracting pollinators in such systems is often poorly understood. In this study, we compared the floral scent of the Eurasian deceptive lady’s slipper orchid Cypripedium calceolus with six co-flowering rewarding species visited by the same pollinators. Cypripedium calceolus produced more floral scent compounds than the co-flowering rewarding species together and differed in the floral scent composition from them. However, C. calceolus shared at least one compound with each co-flowering rewarding species, including widespread and less widespread compounds among flower scents, and had more compounds in common with the co-flowering rewarding species than they had with each other. Several compounds of C. calceolus, such as the aliphatic compounds 1-octanol, octyl acetate, and decyl acetate, did not occur in co-flowering plants but are known as pheromones of pollinating bees. Together, our results suggest that C. calceolus not only emits compounds that are generally common among flowering plants and attractive to many pollinators but specifically imitates floral scent compounds of multiple co-flowering plant species/pheromones of bees. These findings provide valuable insights into the ecology and evolution of floral scent in deceptive pollination systems in orchids.